PANGKALAN TENTARA NASIONAL INDONESIA HALIM PERDANAKUSUMA SEBAGAI BANDARA KOMERSIL DALAM MEWUJUDKAN PROFESIONALISME AWAK PESAWAT - Yohanas Ridwan; Deni D.A.R. (Strategi Pertahanan Udara, 2022)
Halim Perdanakusuma Air Base is not onlt used for military purposes but also for commercial flights. This condition is certainly not an easy matter, especially since it only has one shared runway where the militaru and commercial secter habe their own orientatios. Moreover, where the Halim Perdanakusuma Airfield is always required to be ready to face various threats, considering that currently global dynamics are very developing. For this reason, it is necessary to suppert the professionalism of good flight crews though the implementation of well-scheduled operations and exercise so that the Halim Perdanakusuma Airfield is prepared to face this challenges. The research method used is qualitative method with a phenomenological research desigh. From this study it was concluded that 1) As a multifunctional Air Base, Halim Perdanakusuma needs to be managed properly considering it is quite vulnerable to military and non-military threats, and 2) Halim Perdanakusuma Airbase operations and training in realizing the professionalsm of the flight crew are carried out well even though the are still experiencing problems. Obstacles, including time management, not yet developed good synergy and cooperation, limited facilities and infrastucture, no measurable grand design in the implementation of practice operation and so on. The conclucion is necessary to develop Halom Perdanakusuma Airbase wichi is carried out in a sustainable and structure manner in the managenet of airbase, the addion of a missle unit that functions as a detterent to air attacs, increasing cooperation between the airbase and airport through MoU, grand design specially in operations and training in realizing flight crews also improving facilities and infrastructure to support the existence.Keywords: Exercise, Indonesian, Air force, Operation, Use and Professionalism